1989
DOI: 10.1007/bf00184990
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur and sulphate reduction with acetate and propionate in an aerobic process for sulphide removal

Abstract: Sulphide production rates of sulphurand sulphate-reducing bacteria up to 50 mg per biomass support particle per day were observed in an aerated sulphide-removal reactor with polyurethane (PUR) foam as carrier material. The optimal pH and temperature for the sulphide-producing bacteria were 8.0 and 30°C respectively. Raschig rings and four types of cube-shaped PUR particles were tested as carrier materials. When using PUR particles, the sulphide production rate was always between 3% and 4% of the sulphide remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…This was probably due to an inhibitory effect of sulphide on the heterotrophic organisms present. At 30°C a slight increase in the sulphide effluent concentration was found when fatty acid removal started up, but this effect is due to sulphide production from sulphur and sulphate reduction (Buisman et al 1989c) rather than to an inhibitory effect of the fatty acids.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This was probably due to an inhibitory effect of sulphide on the heterotrophic organisms present. At 30°C a slight increase in the sulphide effluent concentration was found when fatty acid removal started up, but this effect is due to sulphide production from sulphur and sulphate reduction (Buisman et al 1989c) rather than to an inhibitory effect of the fatty acids.…”
Section: Discussionmentioning
confidence: 95%
“…Previously (Buisman et al 1989c) we have shown that anaerobic acetate and propionate oxidation with sulphur and sulphate, respectively, is possible in an aerobic sulphide-removing reactor. The acetate and propionate removal shown in Table 1, however, cannot be due to sulphate-and sulphur-reducing bacteria, because this reducing activity was found to be very low in cell suspensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of acetate and propionate on SRB performance got limited attention so far, and if discussed, it was for other objectives (Buisman et al . ; Omil et al . ; Finke et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, Reyes-Á vila et al [21] using acetate as electron donor indicated that the lithoautotrophic process is faster. Sulfide can be removed via anaerobic processes by chemolithoautotrophic microorganisms such as Thiobacillus denitrificans, which has been extensively studied under anoxic or aerobic conditions [22][23][24]. Sulfide in presence of an organic molecule such as acetate can be removed via denitrification process either in continuous or batch mode [21,25].…”
Section: Introductionmentioning
confidence: 99%